Analysis Of Msmes Performance And Strategy During Covid-19 Pandemic (Case Study on Halwa Cakes in Aceh) - Ahmad Munawar; Husnul Mirzal; Intan Qurratulaini; Fitria Idham Chalid (Universitas Muhammadiyah Jember, 2022)
This study aims to analyze Performance that Including production costs, income, profit and efficiency of Micro, Small and Medium Enterprises (MSMEs) during the Covid-19 Pandemic. In addition, it also aims to know the strategy and factors that affect the results of the efficiency analysis. The research was conducted using a qualitative method with a Case Study approach on home industry businesses with the Halwa Cakes brand, located in Aceh Province. Data obtained by conducting interviews and observations. The results of this study indicate that the total cost of production is IDR 4,337,800 per month, with fixed costs of IDR 28,800 per month and variable costs of IDR 4,050,000 per month. Meanwhile, operating revenues amounted to IDR 7,560,000 with a profit of IDR 3,222,200. The efficiency value of the R / C ratio is 1.74. This means that the Halwa Cake business is considered efficient and profitable even during the Covid-19 Pandemic. This efficiency is influenced by good business and production planning, strategic location and the right product marketing strategy. The results of this study are expected to be useful for MSMEs owners and all related parties as a strategy to survive in time of Covid-19 pandemic.Penelitian ini bertujuan untuk menganalisis performa usaha yang mencakup biaya produksi, pendapatan, keuntungan dan efisiensi dari Usaha Mikro Kecil dan Menengah (UMKM) di masa Pandemi Covid-19. Selain itu penelitian ini juga ingin mengetahui strategi dan faktor yang menyebabkan hasil dari analisis tersebut. penelitian dilakukan dengan metode kualitatif dengan pendekatan studi kasus pada usaha rumah tangga dengan nama Halwa Cakes yang berlokasi di Provinsi Aceh. Pengumpulan data dilakukan dengan wawancara dan observasi. Hasil dari penelitian ini menunjukkan bahwa biaya total produksi adalah 4,337,800 perbulan, yang terdiri dari biaya tetap 28,800 Rupiah dan biaya variabel sebesar 4,050,000 Rupiah. Pendapatan usaha adalah sebesar 7,560,000 dengan keuntungan sebesar 3,222,200 Rupiah perbulan. Nilai efisiensi R/C rasio adalah 1,74, yang artinya usaha Halwa Cakes terhitung efisien dan menguntungkan meski di masa pandem Covid-19. Efisiensi tersebut disebabkan oleh perencanaan bisnis dan produksi yang baik, lokasi usaha yang strategis dan metode pemasaran produk yang tepat. Hasil dari penelitian ini diharapkan bermanfaat bagi pelaku UMKM dan pihak terkait sebagai bagian dari strategi untuk bertahan di masa Pandemi Covid-19.